EDUKASI JAJANAN SEHAT DENGAN METODE EMOTIONAL DEMONSTRATION PADA SISWA SEKOLAH DASAR [EDUCATION OF HEALTHY SNACKS WITH EMOTIONAL DEMONSTRATION METHODS IN PRIMARY SCHOOLS] - Indra Fajarwati Ibnu; Muhammad Syafar; Awaluddin Awaluddin (Jurnal Sinergitas PKM & CSR, 2021)
School children have a habit of buying snacks at school. There are many types of snacks that are generally sold around schools that generally have experienced chemical contamination due to using illegal Food Additives (BTP). This should be a concern because snacks are a part that contributes to food intake for children. Education with the emotional demonstration method (emo demo) is a form of education using a participatory method with the aim of arousing the emotional side of the participants. This activity aims to determine the intention and knowledge of healthy snacks before and after receiving education using the emo demo method. The activity was carried out at an elementary school in Tanah Towa Village, Kajang District, Bulukumba Regency, namely SDN 351 Tanah Towa. There are 37 student participants in class V for each of these schools. The activity method is to provide direct education about healthy snacks using the emo demo method through demonstrations, games and role play. The results of this educational activity using the emo demo method have an influence on increasing the knowledge, attitudes and actions of SDN 351 Tanah Towa students about healthy snacks.BAHASA INDONESIA ABSTRACT: Anak sekolah memiliki kebiasaan membeli jajan di sekolah. Ada banyak jenis jajanan yang umumnya dijual disekitar sekolah yang umumnya telah mengalami pencemaran kimiawi karena menggunakan Bahan Tambahan Pangan (BTP) ilegal. Hal ini harus menjadi perhatian karena jajanan menjadi bagian yang memberi kontribusi asupan pangan pada anak-anak. Edukasi dengan metode emotional demonstration (emo demo) merupakan bentuk edukasi dengan metode partisipatif dengan tujuan menggugah sisi emosional peserta. Kegiatan ini bertujuan untuk mengetahui niat dan pengetahuan tentang jajanan sehat sebelum dan sesudah memperoleh edukasi dengan metode emo demo. Kegiatan dilakukan pada sekolah dasar yang berada di Desa Tanah Towa Kecamatan Kajang Kabupaten Bulukumba yaitu SDN 351 Tanah Towa. Peserta siswa yang berada pada kelas V untuk tiap sekolah tersebut yang berjumlah 37 siswa. Metode kegiatan adalah pemberian edukasi secara langsung tentang jajanan sehat dengan metode emo demo melalui demostrasi, permainan dan role play.  Hasil kegiatan edukasi dengan metode emo demo  ini memberikan pengaruh terhadap peningkatan  pengetahuan, sikap dan tindakan siswa SDN 351 Tanah Towa tentang jajanan sehat.